2015
DOI: 10.1016/j.jbankfin.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The Lintner model revisited: Dividends versus total payouts

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 33 publications
0
19
1
1
Order By: Relevance
“…The international evidence presented in Jacob and Jacob () suggests that tax issues are an important determinant of corporate payout decisions, but that the effects are smaller than reported in previous single‐country studies. We note, though, that results of previous research indicate that tax considerations are not a first‐order determinant in the payout decision of German firms (e.g., Amihud and Murgia, ; Andres et al , , ).…”
Section: Institutional Backgroundcontrasting
confidence: 56%
See 2 more Smart Citations
“…The international evidence presented in Jacob and Jacob () suggests that tax issues are an important determinant of corporate payout decisions, but that the effects are smaller than reported in previous single‐country studies. We note, though, that results of previous research indicate that tax considerations are not a first‐order determinant in the payout decision of German firms (e.g., Amihud and Murgia, ; Andres et al , , ).…”
Section: Institutional Backgroundcontrasting
confidence: 56%
“…Jagannathan et al () provide evidence that dividends are paid out of permanent cash flows while repurchases are paid out of transitory cash flows. Andres et al () support this finding for German firms. Following these results, firms with more volatile cash flows should be more likely to experience transitory changes in cash flows and should thus be more likely to repurchase shares.…”
Section: Hypothesesmentioning
confidence: 77%
See 1 more Smart Citation
“…The study of Javakhadze et al (2014) show that Lintner (1956) dividend smoothing model works internationally, but with cross-sectional differences. Andres et al (2015) also found partial adjustment in dividend is valid in both dividends and total payouts. Notwithstanding the small number of empirical studies which support the irrelevance hypothesis (Bernstein 1996;Black and Scholes 1974;Miller and Rock 1985), there are a number of studies showing that the dividend payout decisions of the company are influential on share prices (Al-Malkawi et al 2010;Kadioglu et al 2015).…”
Section: Literature Reviewmentioning
confidence: 81%
“…54. See Andres, Doumet, Fernau, and Theissen (2015). Jagannathan, Stephens, and Weisbach (2000) and Guay and Harford (2000) provide similar U.S. evidence.…”
Section: Dividends and Share Repurchasesmentioning
confidence: 92%